Prevalencia de Neospora caninum en bovinos en el cantón Guamote. - Guamán Ramírez, Maira Alexandra (2022)
Neospora caninum is a protozoan that affects cattle herds at the reproductive level, having canines as definitive hosts. This protozoan is capable of causing everything from abortions to having malformed babies. The objective of this research is to determine the prevalence of Neospora caninum in cattle from the Guamote canton (Matriz, Cebadas and Palmira). For this, 5 ml of blood samples were taken from the jugular vein of 184 female bovines for their subsequent analysis using the indirect ELISA test. Then, through the chi-square statistical test, the significance and existing correlation between the variables (age, race and height) and the presence of Neospora caninum were analyzed. The results showed that of the 184 cows a total of 28 cases are positive to Neospora, which represents a prevalence of 15.22%. 4.89% of the prevalence according to age corresponds to 5-year-old females, being the age with the highest positive cases; According to the breed, it was observed that most of the infected cases correspond to the Jersey breed with 13 positive animals, which represents a 7.07% prevalence of Neospora caninum; Regarding the height at which each animal is found, 8.70% of prevalence are found at a height of 2750 to 3000 meters above sea level. Finally, based on the results obtained, the prevalence of Neospora caninum in cattle in the Guamote canton is demonstrated, however, in none of the variables under study significant differences were found, that is, race, age and height are not related. with the presence of the disease. Additionally, a sanitary plan is proposed to prevent and control Neosporosis and the application of the proposed plan at the cantonal level is recommended, since it includes several actions to be taken to prevent and control Neosporosis in cattle herds.